KESETARAAN GENDER DALAM TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs): SUATU REVIUW LITERATUR SISTEMATIS - Faturachman Alputra Sudirman; Fera Try Susilawaty (Halu Oleo University, 2022)
Gender equality (SDGs 5) is one of the goals to be achieved in the agenda of the Sustainable Development Goals (SDGs), various problems are still found in the form of gender-based discrimination and inequality in society. Relying on the Scopus database, this study uses a Systematic Literature Review (SLR) approach to investigate, analyze, and present the latest academic literature that focuses on gender equality in sustainable development goals. A total of 74 final documents were determined from 2020-2021, based on the results of network analysis from VOS Viewer, it is known that 3 clusters discuss these issues such as gender equality in the economy, challenges in women's leadership in organizations, women's political participation, women's empowerment and reproductive health. impact on equality in employment opportunities. Thus encouraging the participation of women and girls so that they enjoy equal access to education, economic resources and political participation, and decision-making at all levels is a prerequisite for achieving sustainable development goals.